2016
DOI: 10.1080/13510002.2016.1162431
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of neutral sphingomyelinase decreases elevated levels of nitrative and oxidative stress markers in liver ischemia–reperfusion injury

Abstract: Oxidative stress and excessive nitric oxide production via induction of inducible nitric oxide synthase (NOS)-2 have been shown in the pathogenesis of liver ischemia-reperfusion (IR) injury. Neutral sphingomyelinase (N-SMase)/ceramide pathway can regulate NOS2 expression therefore this study determined the role of selective N-SMase inhibition on nitrative and oxidative stress markers following liver IR injury. Selective N-SMase inhibitor was administered via intraperitoneal injections. Liver IR injury was crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Other studies showed that exogenous ceramide induces NOS2 expression in rat primary astrocytes [113] and reported positive modulation of NOS2 gene expression by SMase and/or ceramide in vascular smooth muscle cells and microglia [114] , [115] . Neutral SMase inhibition decreased both NOS2 and nitrotyrosine levels in an experimental model of glaucoma [116] and liver IR injury [109] . In summary, studies reveal that cellular stress responses significantly increase N-SMase activity and sphingomyelin/ceramide levels, leading to increased nitrative and oxidative modifications.…”
Section: Conceptual and Mechanistic Aspects Of Ros And Oxidative Strementioning
confidence: 95%
See 1 more Smart Citation
“…Other studies showed that exogenous ceramide induces NOS2 expression in rat primary astrocytes [113] and reported positive modulation of NOS2 gene expression by SMase and/or ceramide in vascular smooth muscle cells and microglia [114] , [115] . Neutral SMase inhibition decreased both NOS2 and nitrotyrosine levels in an experimental model of glaucoma [116] and liver IR injury [109] . In summary, studies reveal that cellular stress responses significantly increase N-SMase activity and sphingomyelin/ceramide levels, leading to increased nitrative and oxidative modifications.…”
Section: Conceptual and Mechanistic Aspects Of Ros And Oxidative Strementioning
confidence: 95%
“…Indeed, activation of neutral sphingomyelinase (N-SMase) is reported to be involved in various disease pathologies connected to “oxidative stress”. Studies have shown that ischemia reperfusion (IR) injury leads to activation of N-SMase in rat cardiac myocytes [108] and rat liver [109] . Repletion of glutathione (GSH) via N -acetylcysteine (NAC) treatment in post-myocardial infarction rat hearts resulted in inhibition of N-SMase and decreased oxidative stress resulting in improved left ventricular function [110] .…”
Section: Conceptual and Mechanistic Aspects Of Ros And Oxidative Strementioning
confidence: 99%
“…An optimized multiple reaction monitoring (MRM) method was developed using UFLC coupled with tandem mass spectrometry (MS/MS), as previously described (Unal et al, ). Standards for N ‐palmitoyl‐ d ‐erythro‐sphingosylphosphorylcholine (C16 CerPCho), N ‐stearoyl‐ d ‐erythro‐sphingosylphosphorylcholine (C18 CerPCho), N ‐lignoceroyl‐ d ‐erythro sphingosylphosphorylcholine (C24 CerPCho), N ‐palmitoyl‐ d ‐erythro‐sphingosine (C16 CER), N ‐stearoyl‐ d ‐erythro‐sphingosine (C18 CER), N ‐arachidoyl‐ d ‐erythro‐sphingosine (C20 CER), N ‐behenoyl‐ d ‐erythro‐sphingosine (C22 CER), and N ‐lignoceroyl‐ d ‐erythro‐sphingosine (C24 CER) were purchased from Avanti Polar Lipids (Alabaster, AL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…7 Damage to DNA bases is usually caused by reactive oxygen species (ROS), which include hydroxyl, the superoxide anion, and hydrogen peroxide. 8 , 9 All ROS respond to varying degrees at the initiation of reperfusion as reduced electron carrier molecules of hypoxic cells donate electrons to oxygen during reperfusion. 10 Therefore, effective therapeutic strategies for hepatic ischaemia–reperfusion injury are urgently needed.…”
Section: Introductionmentioning
confidence: 99%